Kajian Ruang Publik Sebagai Sarana Sosialisasi Wanita pada Kawasan Permukiman di Kota Palembang - Tutur Lussetyowati; Listen Prima; Almira Ulfa (Program Studi Arsitektur Fakultas Teknik Universitas Sriwijaya, 2023)
Public space is a space where social and community activities take place. Public spaces will be a place of social interaction. The behavior of people in using public space will be different for each individual and community group. In residential areas, where women spend more time (especially those who don't work) around their home environment, they will use public spaces a lot as a means of socializing with other people. Focus of the study is to find out which public spaces are widely used by women around their neighborhoods and how they use these public spaces as a socialization place. The method uses mix methods that include case study method and field survey method. The results of this study indicate that the public spaces that are mostly used by women around their residential areas are neighborhood roads, markets, stalls, sports fields, and parks. The most usage of public space in residential areas is for necessary activities, such as: shopping; going to work; going to school, and social activities, such as: meeting and chatting with neighbors; and playing with children. Therefore, the output of this research would be a basis of further studied for effectiveness of open public for women.